2020
DOI: 10.3390/jcm9041137
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Genes Associated with Susceptibility to Ovarian Clear Cell Adenocarcinoma Using cis-eQTL Analysis

Abstract: Ovarian clear cell adenocarcinoma (Ov-CCA) has a higher prevalence in the Japanese ancestry than other populations. The ancestral disparities in Ov-CCA prevalence suggests the presence of Ov-CCA-specific genetic alterations and may provide an opportunity to identify the novel genes associated with Ov-CCA tumorigenesis. Using 94 previously reported genes as the phenotypic trait, we conducted multistep expression quantitative trait loci (eQTL) analysis with the HapMap3 project datasets. Four single-nucleotide po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The high frequencies of neoantigens per somatic mutation (neoAg frequencies), rather than overall mutational load or number of predicted neoantigens per se, is an independent prognostic factor for decreased clinical outcome and low expression of immunity-associated genes 219 . Up-regulated rs4873815-TT/ZNF707, ARL4C, mitochondrial superoxide dismutase (SOD2) expression are predictive biomarkers for worse prognosis in OCCC 201 , 220 , 221 . And NAC1/FASN expression is a biomarker of poor outcome for patients treated with conventional platinum-based chemotherapy in OCCC by modulates sensitivity of ovarian cancer cells to cisplatin 203 .…”
Section: Prognosismentioning
confidence: 99%
“…The high frequencies of neoantigens per somatic mutation (neoAg frequencies), rather than overall mutational load or number of predicted neoantigens per se, is an independent prognostic factor for decreased clinical outcome and low expression of immunity-associated genes 219 . Up-regulated rs4873815-TT/ZNF707, ARL4C, mitochondrial superoxide dismutase (SOD2) expression are predictive biomarkers for worse prognosis in OCCC 201 , 220 , 221 . And NAC1/FASN expression is a biomarker of poor outcome for patients treated with conventional platinum-based chemotherapy in OCCC by modulates sensitivity of ovarian cancer cells to cisplatin 203 .…”
Section: Prognosismentioning
confidence: 99%
“…ZNF707 has recently been Kim et al (2020) identified as highly overexpressed in the Japanese population. High expression has also been shown in kidney and luminal B cancer patients Machnik et al (2019) which suggests that ZNF707 could be involved in the development of cancer in general, regardless of the tissue.…”
Section: Highly Connected Genes and Their Possible Relationship With ...mentioning
confidence: 99%